Immune checkpoint inhibitor-related myositis and myocarditis in patients with cancer. (4th September 2018) - Touat, Mehdi; Maisonobe, Thierry; Knauss, Samuel; Ben Hadj Salem, Omar; Hervier, Baptiste; Auré, Karine; Szwebel, Tali-Anne; Kramkimel, Nora; Lethrosne, Claire; Bruch, Jean-Frédéric; Laly, Pauline; Cadranel, Jacques; et al.
Abstract : Objective: To report the clinicopathologic features and outcome of myositis in patients treated with immune checkpoint inhibitors (ICIs) (irMyositis). Methods: We retrospectively analyzed patients diagnosed with irMyositis in tertiary centers in Paris, France, and Berlin, Germany, from January 2015 to July 2017. The main outcomes were clinical manifestations and muscle histology, which included major histocompatibility complex class I (MHC-I), C5b-9, CD3, CD4, CD8, CD20, CD68, programmed cell death protein 1 (PD-1), programmed cell death 1 ligand 1 (PD-L) 1, and programmed cell death 1 ligand 2 (PD-L2). Results: Ten patients with metastatic cancer were included; median age was 73 (range 56–87) years. Median follow-up duration was 48 (range 16–88) weeks. Six patients developed myositis during nivolumab therapy, 1 patient during pembrolizumab, 1 patient during durvalumab, and 2 patients during combined nivolumab and ipilimumab. Median delay between ICI initiation and myositis onset was 25 (range 5–87) days. Clinical manifestations were dominated by acute or subacute myalgia (8 patients) and limb-girdle (7), axial (7), and oculomotor (7) weakness. Four patients had evidence of myocarditis. In all patients, creatine kinase levels were elevated (median 2, 668, range 1, 059–16, 620 U/L), while anti-acetylcholine receptor and myositis-associated antibodies were negative. Electrodiagnostic studies showed myopathic process without decrement in all patients. Muscle biopsy constantly showed multifocal necrotic myofibers, sarcolemmal MHC-I, and endomysial inflammation, consisting mainly of CD68+ cells expressing PD-L1 and CD8+ cells expressing PD-1. ICI treatment was withdrawn in all patients; 9 patients received immunosuppressive therapy, which consistently led to marked clinical improvement. Conclusions: irMyositis presents with remarkably homogeneous and unique clinicopathologic features, expanding the nosologic spectrum of inflammatory myopathies in patients with cancer. ICI withdrawal and treatment with corticosteroids improve outcome.